Enriching surface-enhanced Raman spectral signatures in combined static and plasmonic electrical fields in self-powered substrates. (February 2022) - Li, Haitao; Yin, Hui; Dai, Han; Lee, Hiang Kwee; Cui, Yanying; Sun, Fuwei; Zhang, Yihe; An, Qi
Abstract: Promoting the quality of surface-enhanced Raman spectra (SERS) holds immense significance in various research fields, such as high-sensitive detection or real-time in situ monitoring. However, obtaining rich molecular information from the vibration modes in SERS remains difficult due to the surface selection rules. Herein, we develop an electrically enhanced, composite SERS substrate by combining flower-like Ag nanostructures with a piezoelectric-dielectric polymeric film. The piezoelectricity generated in the polymeric film transforms into combined quasi-static electrical fields with multi-directional distributions and intensified plasmonic hotspots in the Ag nanoflowers. Molecules adsorbed on the Ag nanoflowers are propelled by the quasi-static electrical fields and deviate from the absorption equilibrium states, a key criterion to present additional SERS peaks. In addition, the intensified hotpots generate SERS peaks with higher intensities (> 2 times). Dual-enhanced SERS in both the intensity and the number of vibration peaks e.g., 3 peaks more for 4-Mpy, are obtained from a variety of widely used molecular Raman probes as well as pesticide contaminants. The universality of the dual enhancement effects from our SERS design with increasing detection sensitivity demonstrates high applicability in the rapid and on-site detection of real samples. The changes to SERS spectra, and thus the molecular vibrational fingerprints, in the combined static and plasmonic electrical fields may also inspire scientific understanding in photoelectrical catalytic processes. Graphical Abstract: Simultaneously SERS intensity enhancement and peak enriching effects have been realized on a self-powered SERS substrate comprised by Ag nanoflowers grown on a piezoelectric-dielectric film. ga1 Highlights: A novel self-powered electric-field enriched SERS substrate has been fabricated. This substrate generally allows both enhancing Raman signal and adding characteristic peak under piezoelectric E-field. Such substrate design demonstrates high applicability in the rapid and on-site detection of real samples.